2019
DOI: 10.1002/ecs2.2666
|View full text |Cite
|
Sign up to set email alerts
|

Ecological insights from environmental disturbances in mesophotic coral ecosystems

Abstract: Mesophotic coral ecosystems (MCEs) have historically been considered more stable than shallow reefs and thus suggested to provide refuge to coral reef communities against natural and anthropogenic impacts. Despite this assumption, a growing body of literature has shown that deep reefs are not immune to natural disturbance. Here, based on our in situ observations, we propose that disturbance may actually represent an important mechanism for maintaining biodiversity in MCEs, as is the case for shallow reefs. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Such phenomena suggest that the mesophotic reefs of Eilat may have a potential role as a stable and sheltered environment for scleractinian corals, since corals can reach greater sizes there. However, these conclusions should be approached with caution, since there is evidence that the mesophotic reefs too may not always escape climate-induced disturbances (Eyal et al, 2019;Pinheiro et al, 2019). Indeed, since the mesophotic reefs comprise mostly slow-growing coral growth forms (e.g., encrusting), they are expected to require longer recovery periods after major disturbances, although they are generally considered more robust to physical and thermal stress (Torda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such phenomena suggest that the mesophotic reefs of Eilat may have a potential role as a stable and sheltered environment for scleractinian corals, since corals can reach greater sizes there. However, these conclusions should be approached with caution, since there is evidence that the mesophotic reefs too may not always escape climate-induced disturbances (Eyal et al, 2019;Pinheiro et al, 2019). Indeed, since the mesophotic reefs comprise mostly slow-growing coral growth forms (e.g., encrusting), they are expected to require longer recovery periods after major disturbances, although they are generally considered more robust to physical and thermal stress (Torda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mesophotic corals impacted by tropical storms can be smothered beneath sediment and suffer physical damage, as well as impacted by extreme heatwaves that lead to coral bleaching. Since depth is a well-known factor affecting coral growth, it is expected that the recovery rate from disturbances may differ along a depth gradient (Rocha et al, 2018;Pinheiro et al, 2019). With increasing depth, coral individuals exhibit a decline in their linear extension and calcification rate, due to decreasing levels of photosynthetically-active radiation (Pratchett et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 6, 2020. ; https://doi.org/10.1101/2020.12.04.411496 doi: bioRxiv preprint water reefs can experience impacts from extreme storms and heatwaves, although not at the same frequency or intensity as in the shallow environments [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of MCEs have revealed a dynamic ecology that is prone to shifts in species composition and varied levels of natural disturbances (Rocha et al, 2018;Shepherd et al, 2018b;Pinheiro et al, 2019b). The new species described here, along with two additional recently described species, adds to the high diversity and uniqueness of the fish fauna of Rapa Nui (Shepherd et al, 2018a(Shepherd et al, , 2019.…”
Section: Methodsmentioning
confidence: 99%